Reactions of terminal polyynes with benzyl azide - Luu, Thanh; Medos, Boris J.; Graham, Erin R.; Vallee, Danielle M.; Mcdonald, Robert; Ferguson, Michael J.; Tykwinski, Rik (Journal of Organic Chemistry, 2010)
Terminal di-, tri-, tetra-, and pentaynes substituted with a variety of functional groups react with benzyl azide in the presence of CuSO ·5HO and ascorbic acid to give derivatives of 4-ethynyl-, 4-butadiynyl-, 4-hexatriynyl-, and 4-octatetraynyl-1,2,3-triazoles in moderate to good yields. These reactions appear to proceed regioselectively, and functionalization occurs exclusively at the terminal alkyne moiety. As well, no evidence of multiple azide additions to the polyyne framework is observed. X-ray crystallographic analysis of nine derivatives is used to document the regioselectivity of the reaction as well as outline structural characteristics of the 1,2,3-triazole products. © 2010 American Chemical Society.